2014
DOI: 10.1186/s12866-014-0278-3
|View full text |Cite
|
Sign up to set email alerts
|

Production of potent antimicrobial agent by actinomycete, Streptomyces sannanensis strain SU118 isolated from phoomdi in Loktak Lake of Manipur, India

Abstract: BackgroundActinomycetes have provided a wealth of bioactive secondary metabolites with interesting activities such as antimicrobial, antiviral and anticancer. The study aims at isolation, characterization and the antimicrobial potentiality of Streptomyces sannanensis SU118 obtained from Phoomdi, a unique habitat of Loktak Lake of Manipur, India.ResultsAn actinomycete strain isolated from Phoomdi soil of Loktak Lake of Manipur, India was identified as Streptomyces sannanensis SU118. It is a Gram-positive filame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 48 publications
7
63
0
2
Order By: Relevance
“…Carbon source, like simple sugar in fermentation media enhanced growth as well as bioactive metabolite production rather than more complex carbons. Other finding revealed that the production of antibiotic by S. tanashiensis A2D was preferred in media containing soyabean meal as carbon source 20 . In view of significance of media components, soluble starch and dextrin as carbon sources, malt extract and (NH 4 ) 2 SO 4 as organic and inorganic nitrogen source respectively were chosen as most significant ingredients in the fermentation medium for lincomycin production.…”
Section: Discussionmentioning
confidence: 98%
“…Carbon source, like simple sugar in fermentation media enhanced growth as well as bioactive metabolite production rather than more complex carbons. Other finding revealed that the production of antibiotic by S. tanashiensis A2D was preferred in media containing soyabean meal as carbon source 20 . In view of significance of media components, soluble starch and dextrin as carbon sources, malt extract and (NH 4 ) 2 SO 4 as organic and inorganic nitrogen source respectively were chosen as most significant ingredients in the fermentation medium for lincomycin production.…”
Section: Discussionmentioning
confidence: 98%
“…The organic phase, containing antibiotic compounds, was isolated by a decanter and condensed by heat. The extracted metabolites were used to investigate the anti-cancer activity of the isolates on the breast cancer cell line [11,12]. …”
Section: Extraction Of Metabolites From Actinomycetes Isolatesmentioning
confidence: 99%
“…Filamentous actinomycetes are known to have the ability to produce a wide variety of secondary metabolites [3,4], many of which have useful applications in human and veterinary medicine and agriculture [5], such as enzyme immuno-modulators, antibiotics, insecticides, herbicides, and anticancer agents [6]. Among Actinomycetes, Streptomyces which has long been recognized as a major source of bioactive molecules covers around 70% of the total antibiotic products [7,8]. This genus was confirmed to be promising bacteria against several pathogens and is well known for their potential to produce a large number of inhibitory metabolites used in industry and pharmacy [9].…”
Section: Introductionmentioning
confidence: 99%